Enhancing Scientific Knowledge Depth in Middle School Students through the Woods Model of Science Instruction using Mobile Technology - Ibrahim , Asem Mohammed; Al-Farhan , Ibrahim Ahmed; Ahmed , Eman Wefky; Abdelmagid , Ahmed Sadek; Alomari , Khaled Abdel Kader (International Journal of Interactive Mobile Technologies (iJIM), 2024)
This study aims to investigate the impact of teaching science using the Woods model incorporated into mobile technology on developing the depth of scientific knowledge (DSK) among middle school students. To achieve this goal, a teacher’s guide and student worksheets were prepared for teaching and learning the “Chemistry of Matter” unit from the science book using the Woods model. Additionally, a test was developed to measure the DSK at three levels (recall, concepts and skills, and strategic thinking). The quasi-experimental pre-posttest design was used for two groups, one experimental and the other control. The study sample consisted of 62 students from the third grade of an intermediate school in the Abha region for the academic year 2022–2023, with 30 students in the control group and 32 students in the experimental group. The independent sample t-test, Cohen’s d effect size, and etasquared were used to analyze the research data. The results of the study showed a significant effect size for the utilization of the Woods model in developing the DSK at its three levels. The study recommends the importance of using the Woods model in teaching science at various educational levels.